Clinical Signs and Pathogenesis of Trypanosomal Infection in Human and Animals - Ahmad Rufa’i, Fatihu; Ibrahim Zakari, Abdullahi; Umar, Atikat; Shuaibu, Musayyiba; Alhaji Sani, Ali (Asian Journal of Pharmaceutical Research and Development, 2021)
Trypanosomiasis is a chronic disease which affects both human and animals with high morbidity rate within months after exposure, particularly when poor nutrition or other factors contribute to debilitation. The disease has been a major threat to Human and public health concern and also has contributed negatively to food security in Nigeria. Trypanosomes are haemoflagellated parasites that suppress the host immune system through antigenic variation causing serious illness in man and direct losses in meat production and milk yield in animals leading to severe pathogenesis that result to death . The clinical signs of trypanosomisis have been reported as unnoticed, chronic and acute which can easily lead to death, while the pathogenesis are severe and diverse. A vast majority of human and ruminant animal such as cattle, sheep and goats can be infected without clinical signs. In this paper, we documented some of the major pathogenesis of trypanosomiasis that are leading cause of death and they includes Aneamia, Immunodepression, Immunosuppression, Myocarditis, oedema, loss of conditions, coma as well as infection of various organs and tissues. The paper recommend that further work on pathogenic mechanisms of trypanosomiasis need to be carried out so as to notice the exact clinical sign of the disease which will help towards controlling the disease.